2001
DOI: 10.1139/g01-079
|View full text |Cite
|
Sign up to set email alerts
|

A new meiotic abnormality inZea mays: multiple spindles associated with abnormal cytokinesis in both divisions

Abstract: We report here a new meiotic abnormality recorded in one plant of an inbred line of Zea mays. After an apparently normal prophase I, chromosomes did not congregate in a single metaphase plate. Bivalents remained scattered in the cytoplasm, giving rise to several spindles. Despite the occurrence of multiple spindles, meiosis I proceeded normally, forming a varied number of nuclei at telophase I. The presence of one or a few chromosomes in the nucleus was enough to induce local cytokinesis, which was evident fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In line with this, the spindle assembly checkpoint (SAC) in plants has been found to be less stringent under stress, allowing re-initialization of cell cycle progression upon return to normal conditions 25 . This is further corroborated by several mutants, such as the Arabidopsis atk1 and the maize multipolar spindle (mps) and divergent spindle-1 (dv1) mutant, that all show defective MT dynamics in meiosis, but still complete the meiotic cell division program [26][27][28][29] . At 30-32°C, Arabidopsis thaliana male meiosis exhibits alterations in chiasma formation and chromosome segregation, leading to polyads that harbor aneuploid spores 30,31 .…”
Section: Discussionmentioning
confidence: 89%
“…In line with this, the spindle assembly checkpoint (SAC) in plants has been found to be less stringent under stress, allowing re-initialization of cell cycle progression upon return to normal conditions 25 . This is further corroborated by several mutants, such as the Arabidopsis atk1 and the maize multipolar spindle (mps) and divergent spindle-1 (dv1) mutant, that all show defective MT dynamics in meiosis, but still complete the meiotic cell division program [26][27][28][29] . At 30-32°C, Arabidopsis thaliana male meiosis exhibits alterations in chiasma formation and chromosome segregation, leading to polyads that harbor aneuploid spores 30,31 .…”
Section: Discussionmentioning
confidence: 89%
“…Aberrant meiotic course as a consequence of irregular spindle activity, chromatin transfer among neighbouring PMCs, and chromatin stickiness resulting in abnormal sporads and reduced pollen fertility has been reported in a number of flowering plants (Tilquin et al, 1984;Baum et al, 1992;Caetano-Pereira & Pagliarini, 2001;Mendes-Bonato et al, 2002;Risso-Pascotto et al, 2005;, 2012aKumar et al, 2008aKumar et al, , 2010Kumar et al, , 2011Kumar et al, , 2012Singhal et al, 2008Singhal et al, , 2009aSinghal et al, , 2009bSinghal et al, , 2011aSinghal et al, , 2011bSinghal & Kaur, 2009;Rai & Kumar, 2010;Gulfishan et al, 2010;Himshikha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Proper chromosome segregation is ensured through extensive chromosome reorganisation and the formation of a single and transient spindle during mitosis and meiosis (Caetano-Pereira & Pagliarini, 2001). Spindles that are bipolar in nature differ in their structure in different organisms; however, their basic function is to attach at specific sites called kinetochore and separate the chromosomes/chromatids at anaphases (Wadsworth et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All these events resulted in reduction in pollen fertility. Such an abnormal spindle activity coupled with aberrant synapsis known to affect the meiotic course has also been observed in a number of flowering plants (Tilquin et al 1984, Qu and Vorsa 1999, Caetano-Pereira and Pagliarini 2001, Mendes-Bonato et al 2002, Risso-Pascotto et al 2005, d Erfurth et al 2008, Gulfishan et al 2010, Himshikha et al 2010. Gupta and Yashvir (1973), who have studied the meiotic irregularities in Setaria verticillata, found that the presence of univalents in the species leads to the formation of laggards and chromatin bridges and ultimately affect the meioisis.…”
Section: Discussionmentioning
confidence: 83%